PEMBUATAN VIRGIN COCONUT OIL (VCO) DENGAN METODE TANPA PEMANASAN SEBAGAI UPAYA MENINGKATKAN KESEHATAN MASYARAKAT - Teja Dwi Sutanto; Agus Martono HP; Devi Ratnawati (DHARMA RAFLESIA, 2018)
The aim of this activity was  to training the manufacture of virgin coconut oil (VCO) with a without heating method to the community, especially the mother-housewife, resident of RT 12, Pematang Gubernur, Muara Bangkahulu, Bengkulu. As for the specific targets to be achieved in this activity was for the women, especially mothers, resident of RT 12 has the ability to produce VCO at least for their family, so that can improve the health and well-being of their family. The method used in achieving this goal was by lecture, discussion and practice of making VCO so that these activities target communities to be better understand the method of making VCO and can practice it theirself at home respectively  Keywords: Virgin Coconut Oil, without heating method, public health